How to use a multipurpose SNARE: The emerging role of Snap29 in cellular health - Mastrodonato, Valeria (Cell Stress, 2018)
Despite extensive study, regulation of membrane trafficking is incompletely understood. In particular, the specific role of SNARE (Soluble NSF Attachment REceptor) proteins for distinct trafficking steps and their mechanism of action, beyond the core function in membrane fusion, are still elusive. Snap29 is a SNARE protein related to Snap25 that gathered a lot of attention in recent years. Here, we review the study of Snap29 and its emerging involvement in autophagy, a self eating process that is key to cell adaptation to changing environments, and in other trafficking pathways. We also discuss Snap29 role in synaptic transmission and in cell division, which might extend the repertoire of SNARE-mediated functions. Finally, we present evidence connecting Snap29 to human disease, highlighting the importance of Snap29 function in tissue development and homeostasis.